(untitled) (American Journal of Islam and Society, 2017)
Gilles Kepel is a French political scientist and Arabist with a global reputation for understanding Islam as an ideological, political, and social force. Among his books are Muslim Extremism in Egypt: The Prophet and Pharaoh (1985), Allah in the West: Islamic Movements in America and Europe (1996), Jihad: The Trial of Political Islam (2003), The Roots of Radical Islam (2005), Al Qaeda in Its Own Words (2006; co-edited with Jean-Pereer Milelli), The War for Muslim Minds: Islam and the West (2006), and Beyond Terror and Martyrdom: The Future of the Middle East (2010). In Terror in France: The Rise of Jihad in the West, his latest and bestselling book for 2016, he makes the case that this phenomenon has passed through two phases and recently entered a third one. The first phase began in the 1990s with Mohamed Kelkal and was related to the Algerian civil war. Terrorism was used as a tool to force France to end its support for the coup that had negated the Islamists’ electoral victory. The second phase began in 2012 with the Toulouse and Montauban shootings that were linked to al- Qaeda. Globalization now enabled a network of jihadists linked to Afghanistan to serve the Muslim cause. The (posited) third phase, which would develop after the Arab Spring was launched, would see French jihadists sent to fight ...